Stillbirth in a Tertiary Care Referral Hospital in North Bengal - A Review of Causes, Risk Factors and Prevention Strategies - Shritanu Bhattacharya, (Online Journal of Health & Allied Sciences, 2011)
Background and Aims: Stillbirth is one of the most common adverse outcomes of pregnancy, accounting for half of all perinatal mortality. Each year approximately 4 million stillbirths are reported, with 97% occurring in developing countries. The objective of the present study was to evaluate the stillbirth rate, exploring the risk factors and causes of stillbirth and suggest policies to reduce it. Settings and Design: A retrospective study of stillbirth among all deliveries over 5 years at North Bengal Medical College, a referral tertiary care teaching hospital in a rural background. The stillbirth rate and its trend were defined and the probable causes and risk factors were identified. Results: Stillbirth rate is 59.76/1000 live births, and Perinatal Mortality 98.65/1000 births. Of the still births, 59.72% were fresh and 40.27% were macerated. Among the causes of stillbirths, poor antenatal attendance and low socioeconomic status were important; other risk factors included prematurity, PIH, birth asphyxia, poor intrapartum care including prolonged and obstructed labour. In 23% cases, the cause remained unexplained. Conclusion: In addition to poor antenatal care, low socioeconomic condition, poor referral service, suboptimal intrapartum care in health facilities including tertiary centre were mainly responsible for majority of still births which could have been prevented. We speculate that upgrading the existing health system performance, particularly high quality intrapartum care by skilled health personnel, will reduce stillbirths substantially in our institute.